192k views
3 votes
Solve by using substitution 2x-3y=-12 and x+y=9

User Runes
by
5.4k points

1 Answer

7 votes
Answer: (3,6)

Step-by-step explanation:
So in this question, you have to rearrange the second equation so that either x or y is isolated. I’m going to stick with x for now. First, subtract y from both sides to get x=-y+9. Then, substitute x into the first equation and solve:
2(-y+9)-3y=-12
-2y+18-3y=-12
-5y+18=-12
-5y=-30
y=6
Then, substitute y=6 into any of the 2 equations (preferably the second one) in order to get x:
X+6=9
x=3

You can also check this by substituting x and y into both equations. Hope this helps!
User Phill
by
5.5k points